1997
DOI: 10.1046/j.1365-2249.1997.3761273.x
|View full text |Cite
|
Sign up to set email alerts
|

The systemic lupus erythematosus (SLE) disease autoantigen—calreticulin can inhibit C1q association with immune complexes

Abstract: SUMMARYFollowing its release from cells during infection and inflammation, calreticulin (CRT) can act as an autoantigen in diseases such as SLE. Why CRT is a target of protective immunity and whether it may interfere with innate immunity once released from cells during inflammation is unclear. In the present study, we found that CRT was detected more frequently in SLE sera and in higher amounts than found in control sera. Approximately 40% of SLE sera tested contained autoantibodies against CRT as detected by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
3
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 27 publications
3
48
3
2
Order By: Relevance
“…CRT has also been shown to be associated with the immune response in several ways (37,40). It may be a target for circulating autoantibodies and may contribute to the autoimmune process (37,41,42).…”
Section: Discussionmentioning
confidence: 99%
“…CRT has also been shown to be associated with the immune response in several ways (37,40). It may be a target for circulating autoantibodies and may contribute to the autoimmune process (37,41,42).…”
Section: Discussionmentioning
confidence: 99%
“…Both the collagen-like region [71] and globular heads of C1q [12] have been shown to bind in vitro to the N-terminal half of calreticulin containing the N-and P-domain. Calreticulin has been shown to compete with antibody for binding to C1q and ultimately classical complement activation [5], which may be of consequence in the aetiology of SLE, where immune complex formation and deposition are important. This competition implies that calreticulin and immunoglobulins may have similar binding sites recognized by C1q.…”
Section: Calreticulin and Interaction With The First Component Of Commentioning
confidence: 99%
“…Over the past 10 years, several studies have identified autoantibodies directed against calreticulin in a number of autoimmune diseases, but predominantly in patients suffering from systemic lupus erythematosus (SLE) [2][3][4][5]. Such studies have highlighted a possible role for calreticulin in autoimmunity, especially in immune complex disorders such as SLE.…”
Section: Introductionmentioning
confidence: 99%
“…The identification of a dominant grp78 binding motif on Ro52 (178) and the coexistence of grp78, Ro52 and Ro60 in the surface membrane blebs of apoptotic cells (98) support this view. Interestingly, autoantibodies directed towards grp94/gp96 and calreticulin have also been detected in the sera of patients with SLE (133,179,180) and could perhaps be generated via a similar mechanism.…”
mentioning
confidence: 99%